NATO – between Safety and Security. NATO Summit in Washington – Findings and Concerns - Wojciechowski, Sebastian (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2024)
Safety and security are two distinct, but related and connected issues. While often mistakenly used interchangeably, together they form an integrated safe-secur system that seeks to ensure the maximum safety/security to various entities. Safety is about establishing and maintaining resilience/capability to prevent threats/challenges of a generally unintentional nature, such as natural disasters or accidents. It constitutes a more passive dimension of safety/security, primarily concerned with non-military aspects. To some extent, safety can be likened to a more or less effective defensive shield. Security, on the other hand, is generally about actively countering threats/challenges of a deliberate nature, that is those generated or supported by humans (and in the future, perhaps by artificial intelligence). It often requires physical force or military measures (hard security) to be used in conjunction with the necessary support of soft security, including financial, legal, administrative, and other measures. This dimension of safety/security can therefore be compared to the sword. Despite the above differences, in the case of both safety and security, one can talk about the need, value and purpose of safety/security and the pursuit of interests involved. Both safety and security can be considered internally and externally (internationally), and pointing to a wide variety of related factors. However, the distinction between safety and security is not always clear-cut and different authors perceive it in different ways,1 as illustrated by Clarissa Meerts. In her opinion, safety refers to a state of being free from danger or threat, and is closely related to physical conditions, such as the absence of injury. Security, on the other hand, is more concerned with actions to prevent or respond to external threats (Meerts, 2021). Drawing from the above, certain entities, such as NATO for the purpose of this analysis, can be said to apply security to ensure maximum safety to itself and its members. This article makes the primary reference to the safe-secur (shield and sword) model as a theoretical starting point for discussing the recent NATO Summit in Washington (9-11 July, 2024) and its key outcomes. In this context, a number of research questions arise, such as: (1) To what extent are the Summit’s key outcomes actionable?; (2) Will individual NATO members have the determination, resources, and political will on the one hand, and unity and solidarity on the other to implement them?; (3) Will it be possible in the future to ensure the public support for the implementation of the agreements reached, including high financial costs, especially if the economic and social situation deteriorates or a financial crisis arises?; (4) How will this be affected, for example, by the political crisis ongoing in Germany and France at the end of 2024, the second presidency of Donald Trump starting in 2025, or the further geopolitical reorientation of the United States towards the Indo-Pacific region? These and other research questions are the starting point for the analysis in the text.
Keywords: safety; security; NATO